(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
According to the U.S. Department of Defense, up until December 2022 the Biden Administration has invested approximately 20 billion in security assistance to Ukraine. Part of this total amount has been allocated under the provisions of Public Law 117-118, known as “Ukraine Democracy Defense Lend-Lease Act of 2022”. Passed by the Congress earlier this year, such law clearly evokes the nearly homonymous act of 1941. The essay intends to bring some historical perspective into the analysis of the current U.S. effort to support Ukraine.